2016
DOI: 10.1371/journal.pone.0150212
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Accessory Parotid Gland in the Etiology of Parotitis: Statistical Analysis of Sialographic Features

Abstract: This retrospective study aimed to identify if the existence of the accessory parotid gland correlated with the etiology of parotitis. This may aid the development of better treatment strategies in the future. Sialographic features of cases with parotitis and healthy subjects were reviewed. The chi-square test was used to compare the incidence of accessory parotid gland between the groups. The Student’s t test was used to compare the length of Stensen’s duct, the length from the orifice to the confluence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…Horsburgh et al [ 16 ] in a series of sialographies measured a mean length of Stensen’s duct of 52.0 mm for healthy patients and 53.0 mm in affected patients. Our measurements are slightly higher than the ones found in the literature; a possible explanation has to be found in the type of imaging measurements: as unique studies [ 15 , 16 ] were conducted on sialographies, the major drawback is that it may create a distorted projection and image that differs from true anatomical size.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Horsburgh et al [ 16 ] in a series of sialographies measured a mean length of Stensen’s duct of 52.0 mm for healthy patients and 53.0 mm in affected patients. Our measurements are slightly higher than the ones found in the literature; a possible explanation has to be found in the type of imaging measurements: as unique studies [ 15 , 16 ] were conducted on sialographies, the major drawback is that it may create a distorted projection and image that differs from true anatomical size.…”
Section: Discussioncontrasting
confidence: 68%
“…Stensen’s ducts of the parotid glands of male affected subjects were significantly longer than the ones of control subjects ( p = 0.009 and p = 0.006 for study group 2 and study group 1, respectively). Little information is available in the current literature on the anatomy of Stensen’s duct: in a study conducted by Zhu et al [ 15 ] Stensen’s duct mean length in healthy subjects was shown to be 52.0 mm, while in affected subjects 58.0 mm. Horsburgh et al [ 16 ] in a series of sialographies measured a mean length of Stensen’s duct of 52.0 mm for healthy patients and 53.0 mm in affected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on cadaveric studies, no appreciable histopathological differences from the PGs have been reported (8), and both serous and mucous acini have been identified, suggesting that APG may have similar functions as PGs (9). In most cases, the APG drains into Stensen's duct (parotid duct) through an accessory duct (10). Nonetheless, current guidelines for the delineation of organs at risk (OAR) (11,12) do not account for the APGs, and whether they should be included in the target volume of PGs remains unknown.…”
Section: Introductionmentioning
confidence: 99%